THE INTERVENTION IN ADDITION TRACTION TRANSLATION ELECTRIKAL TRANSCUTANEUS NERVE STIMULATION ULTRASOUND AND EXERCISE MORE QUADRICEPS INCREASE THE SCOPE JOINT MOTION TO OSTEOARTRITIS OF THE KNEE - ISMAIL - (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2013)
Purpose: This study aims to determine the effectiveness of the interventiontranslational addition of traction TENS, Ultrasound (U.S.) and quadriceps exerciseto increase range of motion in knee osteoarthrosis. Methods: The study design was arandomized experimental design with pre test and post test group design, consistingof two groups of samples of the control group by the number of samples obtained asmany as 14 people were given the intervention TENS, Ultrasound (U.S.) andquadriceps exercise, and the group treated with number of samples obtained asmany as 14 people were given the intervention TENS, Ultrasound (U.S.),quadriceps exercise, and Traction Translation. Results: The study used a parametricstatistical analysis of data for LGS flexion and non-parametric statistical analysis ofdata for LGS extension. Based on testing using paired sample t test derived p-value= 0.000 (p value <0.05) for flexion and LGS obtained using the Wilcoxon test pvalue= 0.005 (p value <0.05) for LGS extension means that the interventionUltrasound, TENS and quadriceps exercise can provide increased range of motionflexion and extension are significant for knee OA conditions. Based on testing usingpaired sample t test derived p-value = 0.000 (p value <0.05) for flexion and LGSobtained using the Wilcoxon test p-value = 0.005 (p value <0.05) for LGS extensionmeans that the intervention Ultrasound, TENS, quadriceps exercise and traction canprovide an increase in the scope of the translational motion of flexion and extensionare significant for knee OA conditions. Based on testing using independent sample ttest derived p-value = 0.000 (p value <0.05) and using the Mann-Whitney testvalues obtained p = 0.000 (p value <0.05) which means that the addition oftranslational traction on Ultrasound intervention, TENS, and exercise quadricepswas significantly more effective than intervention Ultrasound, TENS, andquadriceps exercise to increase range of motion flexion and extension on thecondition of osteoarthritis of the knee. Conclusion: The addition of translationaltraction on intervention Ultrasound, TENS, and exercise quadriceps further increaserange of motion flexion and extension on the condition of osteoarthritis of the knee